PERANCANGAN MOTION GRAPHIC SEBAGAI IKLAN LAYANAN PENTINGNYA IMUNISASI BAGI ANAK SEJAK USIA DINI DI KOTA BUKITTINGGI - RAYHAN HELSA FAJRI, Dra. Zubaidah, M.Sn., Elia Pebriyeni, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Immunization is a process of providing of immunity to infants or toddlers by inoculating a live microbial vaccine. The function of immunization is to prevent diseases such as hepatitis, diphtheria, polio, tuberculosis, tetanus, measles and infectious diseases that can harm infants and children. Cumulative immunization case reports issued by PP & PL Public Health Office until 2016 shows that 73% of coverage of complete basic immunization in Bukittinggi is still far from expectation. This is due to the lack of knowledge of the people of Bukittinggi city about immunization. The spread of the issue raises anxiety towards parents, especially mo hers, until they are hesitant to give vaccines to children. There are so many dangers and risks of infectious diseases that can harm infants and children because of not giving immunization from an early age. To overcome this people, there is a need in a media to socialize to the public about the dangers of not immunizing for children from an early age. The method of designing idea in collecting data is by visiting, observing and interviewing Public Health Center, Rasimah Ahmad, Bukittinggi. While the method of data analysis is 5W1H analysis by studying What? Who? When? Where? Why? and How? on motion graphic design as a public service advertisement. The purpose of the final project is to design public service announcement media in a motion graphic so the people of Bukittinggi city can realize the impact of not giving immunization for children from an early age, help increasing the awareness of mothers of age of 20 years old up to 40 years old of about immunization and help the Public Health Office in Bukittinggi in generating public interest, especially mothers about the importance of immunization. The design of Public Service Announcement about the Importance of Immunization for Children at Early Age in Bukittinggi City in a Motion Graphic serve as the primary media, and the supporting media are CD Cover, CD label, Poster, Towel, X-banner, Clothes, Tote Bag, and Snapback. Keyword: Immunization, Bukittinggi, ILM, Motion Graphic.